The Correlation Between Educational Attainment and Duration of Breast-feeding of Women Fertil in Rural Banggai Regency - S Otoluwa, Anang; Monoarfa, Yustiyanty; Kurniasari, Dian; Forsberg, Neil (Mulawarman International Conference on Tropical Public Health, 2025)
Background : The Government of Indonesia has recently initiated a national effort to reduce incidence of child stunting. One of the important effort to reduce stunting is breastfeeding practice. Objective : To evaluate the correlation between the level of education and duration of breast feeding on women fertile in Banggai Regency. Research Methods/ Implementation Methods : A sample of 454 women in children bearing from twenty villages contained with Banggai Regency were selected to participate in this study. Variables included duration of breastfeeding, mothers education level, mothers ages. Data was analysed using binary logistic regression. Results : The data indicate that large proportions (near 45%) of women completed only elementary school. Approximately 30% of the women had completed high school. Most women breast-fed for over six months. Less than 15% of the women in all villages breast-fed for less than 6 months. There was a significant positive correlation between educational attainment and duration of breast-feeding (P<.0455). Conclusion/Lesson Learned : Educational attainment has positive correlation to the duration of breastfeeding.